Abandonment of grazing in a mediterranean grassland area: consequences for ant assemblages - Azcárate, Francisco M.; Peco, Begoña (Insect Conservation and Diversity, 2012)
1. Abandonment of traditional activities in the rural areas is widespread in the developed world, and in the case of grazing, it is known to have negative consequences on the diversity of plant communities. Few studies have examined the impact of grazing abandonment on fauna, which in the case of ants is of considerable interest, given their usefulness as an indicator for monitoring environmental change. 2. Here, we present the results of a study conducted in Mediterranean grasslands of central Spain. Using pitfall traps, ants were sampled from 10 40 m· 20 m plots; ﬁve of them located in grazed systems and ﬁve in abandoned grazing systems. Descriptors used for the ant assemblage were ant species composition, ant species richness, ant functional groups, and subguilds of granivores. We used a seed bait test to discriminate between granivorous and non-granivorous ant species. 3. Our results show that abandoned grazing systems have more ant species and more heterogeneous ant assemblages. Changes in ant species composition and ant functional groups are more pronounced in habitats where woody encroachment progresses more rapidly (i.e. dry sectors and tree islands). Specialised granivores have reduced importance in the same habitat types. Conversely, facultative granivores increase their presence in abandoned grazing systems. 4. The increased functional and species ant diversity observed with grazing abandonment can be explained by the generation of a more heterogeneous environment at the smaller scales, in spite of being more homogenous at the larger scales, because the latter are less signiﬁcant for the organisms studied
Keywords: ant functional groups; Ants; Granivory; grazing abandonment; mediterranean grasslands

Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region - Quézel, Pierre (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements
Keywords: annual grasslands; broadleaved forests; circum-Mediterranean; Holocene; matorrals and steppes; Mediterranean flora; mediterranean grasslands; Mediterranean vegetation; post-glacial distribution; pre-steppe-forests (citation)

Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region - Quézel, Pierre (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements
The following values have no corresponding Zotero field: periodical: Recent Dynamics of the Mediterranean Vegetation and Landscape electronic-resource-num: 10.1002/0470093714.ch1
Keywords: annual grasslands; broadleaved forests; circum-Mediterranean; Holocene; matorrals and steppes; Mediterranean flora; mediterranean grasslands; Mediterranean vegetation; post-glacial distribution; pre-steppe-forests (citation)

Assessment of the effects of ozone exposure and plant competition on the reproductive ability of three therophytic clover species from Iberian pastures - Gimeno, B S; Bermejo, V; Sanz, J; de la Torre, D; Gil, J M (Atmospheric Environment, 2004)
Ozone (O3 ) phytototoxicity has been reported on a wide range of crops and wild Central European plant species, however no information has been provided regarding the sensitivity of plant species from dehesa Mediterranean therophytic grasslands in spite of their great plant species richness and the high O3 levels that are recorded in this area. A study was carried out in open-top chambers (OTCs) to assess the effects of O3 and competition on the reproductive ability of three clover species: Trifolium cherleri, Trifolium subterraneum and Trifolium striatum. A phytometer approach was followed, therefore plants of these species were grown in mesoscosms composed of monocultures of four plants of each species, of three plants of each species competing against a Briza maxima individual or of a single plant of each clover species competing with three B. maxima plants. Three O3 treatments were adopted: charcoal ﬁltered air (CFA), non-ﬁltered air (NFA) and non-ﬁltered air supplemented with 40 nl l 1 of O3 (NFA+). The different mesocosms were exposed to the different O3 treatments for 45 days and then they remained in the open. Ozone exposure caused reductions in the ﬂower biomass of the three clover species assessed. In the case of T. cherleri and T. subterraneum this effect was found following their exposure to the different O3 treatments during their vegetative period. An attenuation of these effects was found when the plants remained in the open. Ozone-induced detrimental effects on the seed output of T. striatum were also observed. The ﬂower biomass of the clover plants grown in monocultures was greater than when competing with one or three B. maxima individuals. An increased ﬂower biomass was found in the CFA monoculture mesocosms of T. cherleri when compared with the remaining mesocosms, once the plants were exposed in the open for 60 days. The implications of these effects on the performance of dehesa acid grasslands and for the definition of O3 critical levels is discussed
Keywords: Critical levels; Dehesa; flower biomass; mediterranean grasslands; seed production

Herbivorous mammals as seed dispersers in a Mediterranean dehesa - Malo, Juan E; Suárez, Francisco (Oecologia, 1995)
Endozoochorous seed dispersal by herbivo- rous mammals has been verified repeatedly and its possi- ble influence on the structure and function of herbaceous communities has been suggested. Quantitative studies, however, are lacking in the field of seed dispersal via the dung of herbivore guilds in little-altered environments. The present paper analyses seed dispersal via rabbit, fal- low deer, red deer and cow dung in a Mediterranean de- hesa (open woodland used for hunting and ranching) during the seeding season. Dung seed content was deter- mined by the glasshouse cultivation of eight dung sam- ples from each herbivore, collected fortnightly between February and August. The four herbivores disperse many seeds (spring averages are 6-15 seeds per gram of dry dung and maxima of 25-70) from a large number of spe- cies (totals between 52 and 78). Dispersal seems to be mainly determined by seed production of the plant com- munity. This is reflected in (i) the dissemination of a high percentage of the species present in the dehesa, (ii) great seasonal variability, related to seed production, in the amount of seeds and number of species dispersed, and (iii) a high semi-quantitative similarity of seed con- tent in the four types of herbivore dung throughout the year. There is also important quantitative variation that depends on animal traits and feeding habits. These re- sults and the characteristics of species found in dung suggest the adaptation of plant species to the dispersal of their seeds via herbivore gut. This process may well have profound implications for vegetation dynamics and the evolution of plant traits.
Keywords: endozoochory; mediterranean grasslands; pasture dynamics; seed dispersal; Therophytes

Differences between oligotrophic communities resulting from old-field succession in relation to bedrock - Puerto, A.; Rico, M. (Plant Ecology, 1994)
Dehesa ecosystems on granite and on slate clearly differ in soil characteristics. Our aim was to find out whether floristic composition differed too. We selected an equal number of plots, on both granite and slate, in different successional stages of development and at various ages after field abandonment (the youngest 15-20 years). Plots with rock-outcrops, which had never been cultivated, were also included in the study. The results showed that floristic differences between granite and slate communities were not detectable in the younger successional stages. However, they showed up with time and on stabilized grasslands became significant. But on plots with rock-outcrops the differences were not observable. This was undoubtedly influenced by the peculiar features of these plots, characterised by poor arid soils and surface parent material. In fact they did not show significant differences in the analysed soil parameters either. Species diversity and biomass showed a similar pattern of differences to floristic composition. The highest species diversity was found on plots with lower biomass (the youngest ones). The lowest biomass in conjunction with quite low species diversity was found on plots with rock-outcrops, which again is consistent with their peculiar features.
Keywords: biomass; diversity; granite; mediterranean grasslands; slate

Differences between oligotrophic communities resulting from old-field succession in relation to bedrock - Puerto, A; Rico, M (Plant Ecology, 1994)
Dehesa ecosystems on granite and on slate clearly differ in soil characteristics. Our aim was to find out whether floristic composition differed too. We selected an equal number of plots, on both granite and slate, in different successional stages of development and at various ages after field abandonment (the youngest 15-20 years). Plots with rock-outcrops, which had never been cultivated, were also included in the study. The results showed that floristic differences between granite and slate communities were not detectable in the younger successional stages. However, they showed up with time and on stabilized grasslands became significant. But on plots with rock-outcrops the differences were not observable. This was undoubtedly influenced by the peculiar features of these plots, characterised by poor arid soils and surface parent material. In fact they did not show significant differences in the analysed soil parameters either. Species diversity and biomass showed a similar pattern of differences to floristic composition. The highest species diversity was found on plots with lower biomass (the youngest ones). The lowest biomass in conjunction with quite low species diversity was found on plots with rock-outcrops, which again is consistent with their peculiar features.
Keywords: biomass; diversity; granite; mediterranean grasslands; slate